A Review on Current Innovation in Space Medicine: Review Article (Journal of Pharma Insights and Research, 2024)
Space exploration presents unique challenges to human health and well-being, which demand specialized medical research and intervention strategies. Space medicine is a field that involves the prevention, diagnosis, and treatment of medical conditions that arise during the space mission. Astronauts are facing so many health issues due to microgravity, space radiation, isolation and confinement, gravity fields, and hostile and closed environments. In space, the stability of drugs is also affected. The present data indicates that physiological changes occurring during space missions might certainly alter drug potency, efficacy, and safety, which rely on the drug, formulation, duration of space travel, and environmental conditions. With no possibility of resupply, researchers are grappling with the shelf life of the existing pharmaceuticals. The current state of medicine in space is all about storage, management, and adopting conventional medicinal manufacturing in space. In recent days, some innovative research has focused on personalized medicine with the aid of biomarkers, fabricating medicine in space, and genetically modified approaches. The future of space medicine will be characterized by innovation, collaboration, advancing human healthy and exploration beyond the earth’s atmosphere